Response of mango cultivars to agro-chemicals in relation to yield attributes (Indian Journal of Arid Horticulture, 2021)
Mango has wide adaptability, high nutritive value, richness in variety, delicious taste, pleasant flavour, attractive appearance and it enjoys the unique popularity among the masses and classes. Mango fruits are rich in vitamin A and C. Application of agro-chemicals alter the behavior of trees for the economic benefit of the fruit growers. In this regard an experiment was conducted at Agriculture Research Station, Banswara district of Rajasthan to find out the response of different agro-chemicals. The experiment consisted of thirteen treatments along with control and replicated thrice in a Randomized Block Design. Fifteen years old mango orchard was selected for experiment which has Dashehari, Langra and Kesar. Plants were planted with square system of planting at 10 m × 10 m spacing. Agro-chemicals viz., calcium chloride (0.3, 0.6 & 0.9%), potassium nitrate (1, 2 & 3%), paclobutrazol (500, 1000 & 1500 ppm), sorbitol (1.5, 2.0 & 2.5%) and control-water spray were used at different stages and time. Among alternate bearing mango cultivars (Dashehari, Langra and Kesar), cultivar Kesar recorded higher fruit weight while Langra recorded higher fruit yield over Dashehari. Fruit diameter significantly influenced by agro-chemicals. Yield per tree and estimated yield per hectare were enhanced by application of paclobutrazol 1500 ppm.